2006
DOI: 10.1152/ajpcell.00353.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate activates BKCa channels independently of G protein-coupled receptor in human endothelial cells

Abstract: The effect of sphingosine-1-phosphate (S1P) on large-conductance Ca(2+)-activated K(+) (BK(Ca)) channels was examined in primary cultured human umbilical vein endothelial cells by measuring intracellular Ca(2+) concentration ([Ca(2+)](i)), whole cell membrane currents, and single-channel activity. In nystatin-perforated current-clamped cells, S1P hyperpolarized the membrane and simultaneously increased [Ca(2+)](i). [Ca(2+)](i) and membrane potentials were strongly correlated. In whole cell clamped cells, BK(Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…In addition, OxLDL or LPC might increase the sensitivity of BKCa channels to Ca 2+ , because OxLDL or LPC augmented BKCa current further which was already activated by clamping [Ca 2+ ]i to 1 μM. BKCa current activation can hyperpolarize membrane, thereby increasing the driving force for Ca 2+ Kim et al, 2006 ]i. These effects of OxLDL on HUVECs are mimicked by its main lipid constituent LPC, and therefore, LPC mediates these responses on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, OxLDL or LPC might increase the sensitivity of BKCa channels to Ca 2+ , because OxLDL or LPC augmented BKCa current further which was already activated by clamping [Ca 2+ ]i to 1 μM. BKCa current activation can hyperpolarize membrane, thereby increasing the driving force for Ca 2+ Kim et al, 2006 ]i. These effects of OxLDL on HUVECs are mimicked by its main lipid constituent LPC, and therefore, LPC mediates these responses on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, S1P generated in muscles may be able to diffuse to motor neurons, but likely acts by a mechanism independent of known S1P receptors. S1P can interact with multiple intracellular targets, including transient receptor potential (TRP) channels, store-operated calcium channels, inositol triphosphate receptors, and calcium-activated potassium channels (BK Ca ) (Ghosh et al 1994;Mattie et al 1994;Flemming et al 2006;Kim et al 2006). Although these targets are found in neurons, the functional significance of their interaction with S1P on neurotransmitter release is not known.…”
Section: Sphk-1 Positively Regulates Ach Releasementioning
confidence: 99%
“…However, other studies found the involvement of S1P1 receptors in the regulation of contractile reactivity [44][47] and S1P agonist were found recently to evoke vasoconstriction of the afferent renal arterioles via S1P1 and S1P2 receptors with involvement of the L-type voltage-dependent calcium channels [48]. Further, S1P induces COX-2 expression in vascular smooth muscle cells, which seems partially mediated via S1P1 receptors [49].…”
Section: Discussionmentioning
confidence: 98%
“…The comparable effect of both FTY720 and SEW2871 on vascular contractility suggests the involvement of S1P 1 receptor-dependent mechanism, whereas vascular smooth muscle were reported to express mainly S1P2 and S1P3 receptors that mediate vasoconstriction [40][43] through activation of the phospholipase C, myosin light chain kinase and/or Rho-associated kinase-dependent inhibition of myosin light chain phosphatase [44][47]. However, other studies found the involvement of S1P1 receptors in the regulation of contractile reactivity [44][47] and S1P agonist were found recently to evoke vasoconstriction of the afferent renal arterioles via S1P1 and S1P2 receptors with involvement of the L-type voltage-dependent calcium channels [48].…”
Section: Discussionmentioning
confidence: 99%